An increase of fractional exhaled nitric oxide after specific inhalation challenge is highly predictive of occupational asthma - Engel, Julia; van Kampen, Vera; Lotz, Anne; Abramowski, Jessica; Gering, Vitali; Hagemeyer, Olaf; Brüning, Thomas; Raulf, Monika; Merget, Rolf (International archives of occupational and environmental health, 2018)
Purpose An increase of fractional exhaled nitric oxide (FeNO) has been described after specific inhalation challenges (SICs) with occupational allergens, but the clinical role of FeNO measurements before and after SIC is unknown. It was the aim of this study to assess the diagnostic accuracy of FeNO measurements before and after SIC in subjects with suspected occupational asthma (OA). Methods One hundred forty-eight patients with suspected OA were examined by SIC with various occupational allergens. Subjects were assigned to pulmonary responders, nonresponders or doubtful by standard lung function criteria. FeNO was measured before SIC (baseline) and 24 h afterwards. Subjects with negative or doubtful SIC but increase of FeNO were evaluated individually by an overall expert rating. Effect modifiers of FeNO increases were assessed by regression analyses. Results Thirty-one patients (21%) were classified as pulmonary responders, 105 (71%) as nonresponders and 12 (8%) as doubtful. With the pulmonary responder status as gold standard an increase of FeNO ≥ 13 ppb showed a specificity of 0.9 and a sensitivity of 0.5. Seventeen subjects with negative or doubtful responder status showed such an increase of FeNO, among them 13 subjects with definitive or probable OA after expert rating. Regression analyses revealed no significant modifiers for the FeNO increase. Conclusion An increase of FeNO after SIC is highly predictive of OA and should be regarded as an additional criterion for the interpretation of SIC with occupational agents.